263 Clinical Features of Drug Rash with Eosinophilia and Systemic Symptoms Syndrome Caused by Antituberculous Medications - Kim, Sang-Ha (World Allergy Organization Journal, 2012)
BACKGROUND: Drug rash with eosinophilia and systemic symptoms (DRESS) syndrome is one of severe adverse drug reactions. Aromatic anticonvulsants and sulfonamides are the most common causes of DRESS syndrome. However, there have been only 2 case reports of DRESS syndrome induced by antituberculous medication. This study was aimed to observe the clinical features of patients with DRESS syndrome caused by antituberculous medications. METHODS: We retrospectively revealed the clinical and laboratory data of the patients from September 2006 to August 2010 at a University Hospital. Our patients were diagnosed as DRESS syndrome if 3 criteria were present: (1) cutaneous drug eruption, (2) peripheral eosinophilia >1,500/μL, (3) systemic involvement (lymphadenopathy, hepatitis or fever). RESULTS: Nine patients (5 men, 4 women; mean age 50.5 years) were enrolled DRESS syndrome induced by antituberculous medications. The most common causative agent was ethambutol which was identified as the cause in 8 of 9 patients (88.9%). In the other patient, streptomycin was considered as the causative agent. Two out of 8 patients with DRESS syndrome caused by ethambutol were induced by rifampicin as well. Drug eruption developed 6.9 weeks after antituberculous drugs were first used. Skin eruptions were involved on the whole body in 8 patients and on only upper trunk in 1 patient. Diffuse maculopapular eruption was the most common type of skin lesions that was observed in 8 of 9 patients. Other types of skin eruption were identified; 4 exfoliative eruptions, 3 facial edema and 1 urticaria. The mean value of peripheral eosinophil counts was 3,354/μL. The cervical, axillary or inguinal lymphadenopathy was observed in 7 patients and fever was detected in 6 patients. Hepatitis was developed in 3 patients. All patients with DRESS syndrome recovered after corticosteroid therapy and the elimination of the culprit drugs. CONCLUSIONS: The most common cause of DRESS syndrome induced by antituberculous medications was ethambutol in our study. Diffuse maculopapular eruption on the whole body was the most common type of eruption and lymphadenopathy was the most common involvement of internal organ in patients with DRESS syndrome caused by antituberculous drugs.